Animals in the Locality: Environmental Disaster, Disability and Human–Animal Spatial Identity Politics in Indra Sinha’s Animal’s People (2007) - Sarkar, Barnali (Journal of Advanced Research in Social Sciences, 2022)
The concept of disability has often been chained to that of animality as humanness is regarded as inherently marked by independence and rationality, the lack of which in animate beings is randomly associated with animality. The animality/humanity dualism, championed by anthropocentrism and ableism, not only affects the identity of humans with special needs by grouping them as Others but also disregards the agency of animals/nonhumans and nature by denying human dependency on and similarities with more-than-human entities. This research in its exploration of the connection between disability and ambiguous identity will focus upon the dynamics of the animality/humanity dualism in the context of an industrial disaster and ensuing disability as represented in Indra Sinha’s Animal’s People (2007). By understanding animality/humanity binary through the lens of local/global spatial distinction, the article scrutinises the way the animal/human ambiguous sense of place of the protagonist is mediated by his spatial relations. Building on both critical disability scholarship on animalisation of disabled humans and bioregional exploration of local/global spatial boundaries, the research, therefore, contends that the impact of environmental disasters on certain human groups creates a local (deformed humans as animals)/global (elite humans) spatial binary. The resolvability of such binaries, as the research further argues, is coterminous with developing a local bioregion, which is both connected to and dissociated from global/international places and is built upon humans–nonhumans/animals/nature interrelations that allow an agentic and inclusive human–nonhuman sense of belonging in the region.